Discovery and settlement : Europe meets the New World, 1490-1700 - Brown, Gene. (New York : Twenty-First Century Books, 1993)
Presents primary source materials related to the discovery and settlement of America and daily life in the colonies, including the experiences of Native Americans, African Americans, and women.
Includes bibliographical references (p. 62) and index.
Keywords: Minorities -- United States -- History -- 17th century -- Sources -- Juvenile literature; Minorities -- United States -- History -- 18th century -- Sources -- Juvenile literature; Minorities -- History -- Sources; United States -- History -- Colonial period, ca. 1600-1775 -- Sources -- Juvenile literature; America -- Discovery and exploration -- Sources -- Juvenile literature; America -- Discovery and exploration -- Sources; United States -- History -- Colonial period, ca. 1600-1775 -- Sources